A Generalized Language for Platform-Independent Structured Reporting - Kahn, C. E., Jr. (Methods of Information in Medicine, 1997)
Structured reporting systems allow health-care workers to record observations using predetermined data elements and formats. The author developed the Data-entry and Reporting Markup Language (DRML) to provide a generalized representational language for describing concepts to be included in structured reporting applications. DRML is based on the Standard Generalized Markup Language (SGML), an internationally accepted standard for document interchange. The use of DRML is demonstrated with the SPIDER system, which uses public-domain Internet technology for structured data entry and reporting. SPIDER uses DRML documents to create structured data-entry forms, outline-format textual reports, and datasets for analysis of aggregate results. Applications of DRML include its use in radiology results reporting and a health status questionnaire. DRML allows system designers to create a wide variety of clinical reporting applications and survey instruments, and helps overcome some of the limitations seen in earlier structured reporting systems.
Keywords: Computer-based Patient Records; Structured Data Entry; Reporting; Standards; SGML; World Wide Web; Knowledge Representation